Fabrication of g-C3N4 Nanosheets Anchored With Controllable CdS Nanoparticles for Enhanced Visible-Light Photocatalytic Performance - Wang, Minggui; Wang, Min; Peng, Fang; Sun, Xiaohuan; Han, Jie (Frontiers in Chemistry, 2021)
Herein, g-C3N4/CdS hybrids with CdS nanoparticles anchoring on g-C3N4 nanosheets were constructed. The effects of CdS nanoparticles on photocatalytic H2 production and organic molecules degradation for g-C3N4/CdS hybrids were investigated. The maximum rate of H2 production for g-C3N4/CdS sample was 1070.9 μmol g-1 h-1, which was about four times higher than that for g-C3N4 nanosheets sample. The enhanced photocatalytic performance for prepared hybrids could be mainly attributed to the following causes: the formed heterojunctions can contribute to the light absorption and separation of photogenerated electrons and holes, two-dimensional layered structure facilitates the transmission and transfer of electrons, and high specific surface area could provide more exposed active sites.